Predictive factors of advanced chronic kidney disease in children with congenital anomalies of kidney and urinary tract - Dea Puspitarini; Elisabeth Siti Herini; Cahya Dewi Satria; Kristia Hermawan (Paediatrica Indonesiana, 2023)
Background Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease (CKD) in children. Delayed diagnosis of CAKUT due to lack of universal screening (such as prenatal ultrasound screening or postnatal ultrasound screening in neonates with risk of CAKUT) has led to more cases of advanced CKD in children. CKD has high morbidity and mortality, and early detection is required to prevent the progression of CKD. Objective To determine the factors that predict the development of advanced CKD in children with CAKUT. Methods This retrospective cohort study included children with CAKUT at Dr. Sardjito Hospital, Yogyakarta, Indonesia from January 2016 to February 2021. Patients who were diagnosed with CAKUT were followed up to 5 years or until the onset of advanced CKD. Advanced CKD was defined as a decreased estimated glomerular filtration rate (eGFR) of less than 30mL/min/1.73m2 based on the revised Schwartz formula. CKD progression-free survival was determined with Kaplan-Meier and Cox regression analyses. Results Among 62 subjects with CAKUT, 7 (11.3%) subjects progressed to advanced CKD. The mean time of advanced CKD progression was 52.2 (95%CI 46.9 to 57.5) months. The overall incidence rate was 22 per 1,000 person-years. Based on Kaplan-Meier analysis, children with eGFR <60 mL/min/1.73m2 at the time of diagnosis had more rapid progression to advanced CKD than patients with eGFR ?60 mL/min/1.73m2 [40.2 (95%CI 33.4 to 46.6) months vs. 58.2 95%CI 46.9 to 57.5) months; P=0.02, respectively]. Conclusion Reduced eGFR at the time of diagnosis showed rapid progression to advanced CKD.